Free Radical, Carbonyl, and Nicotine Levels Produced by Juul Electronic Cigarettes. Issue 9 (20th October 2018) - Reilly, Samantha M; Bitzer, Zachary T; Goel, Reema; Trushin, Neil; Richie, John P
Abstract: Introduction: Free radicals and carbonyls produced by electronic cigarettes (e-cigs) have the potential to inflict oxidative stress. Recently, Juul e-cigs have risen drastically in popularity; however, there is no data on nicotine and oxidant yields from this new e-cig design. Methods: Aerosol generated from four different Juul flavors was analyzed for carbonyls, nicotine, and free radicals. The e-liquids were analyzed for propylene glycol (PG) and glycerol (GLY) concentrations. To determine the effects of e-liquid on oxidant production, Juul pods were refilled with nicotine-free 30:70 or 60:40 PG:GLY with or without citral. Results: No significant differences were found in nicotine (164 ± 41 µg/puff), free radical (5.85 ± 1.20 pmol/puff), formaldehyde (0.20 ± 0.10 µg/puff), and acetone (0.20 ± 0.05 µg/puff) levels between flavors. The PG:GLY ratio in e-liquids was 30:70 across all flavors with GLY being slightly higher in tobacco and mint flavors. In general, when Juul e-liquids were replaced with nicotine-free 60:40 PG:GLY, oxidant production increased up to 190% and, with addition of citral, increased even further. Conclusions: Juul devices produce free radicals and carbonyls, albeit, at levels substantially lower than those observed in other e-cig products, an effect only partially because of a low PG:GLY ratio. Nicotine delivery by these devices was as high as or higher than the levels previously reported from cigarettes. Implications: These findings suggest that oxidative stress and/or damage resulting from Juul use may be lower than that from cigarettes or other e-cig devices; however, the high nicotine levels are suggestive of a greater addiction potential.